Fumigant activity of Schinus terebinthifolius essential oil and its selected constituents against Rhyzopertha dominica (2018)
The aim of the present study was to evaluate the insecticidal potential of the essential oil from ripened and unripened fruit of the plant Schinus terebinthifolius and compare the toxic effects of artificial blends made with selected constituents of these oils [limonene, (E)-nerolidol, α-terpineol, β-terpineol, terpinolene, α-pinene and β-pinene] on the lesser grain borer, Rhyzopertha dominica (family -order). No statistically significant difference was found between the oils in the time periods tested (24, 48 and 72 h). Rhyzopertha dominica was more susceptible to limonene, terpinolene, α-pinene and β-pinene. Among the complete artificial blends tested at the proportions identified chemically, only that prepared with the constituents of the ripened fruit oil demonstrated toxicity on the same level as the essential oil. The analysis of the constituents revealed that limonene and α-terpineol contributed most to toxicity of the ripened fruit oil, whereas only limonene contributed to the toxicity of the unripened fruit oil. The present findings demonstrate that the toxicity of the ripened and unripened fruit oils cannot be attributed only to the individual toxicity of the constituents, but also the proportion at which these compounds are found and the types of interactions among the compounds.